Evaluating the Growth of Village Revenue by Enhancing Village-Owned Enterprises (BUMDes) Through the Application of Good Corporate Governance - Adriyana, Rika; Affa, Ahmad Syaiful; Surendra; Pramestu, Meidiastika Widya (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
This Badan Usaha Milik Desa (BUMDes) is a business entity where all or most of its capital is owned by the village through direct investment derived from the separated wealth of the village to manage assets, service provision, and other. BUMDes or village-owned enterprises represent an innovation for each village to continuously enhance their Village Original Income (PADes). This research aims to describe the optimization of BUMDes management by applying the principles of good governance, namely cooperative, participative, emancipative, accountable, transparent, and sustainable. Based on field surveys, questionnaire distribution, and interviews with several BUMDes managers, the results indicate that BUMDes has implemented aspects of good governance well. However, there are aspects that have not been optimally performed, such as accountability in financial reporting not being in line with accounting standards. As BUMDes Sumurjomblangbogo falls under the category of being in the pioneering stage, it has not yet contributed to the Village Original Income (PADes).